Climbing Information System Design Web-Based Mount Gede Pangrango Using the Waterfall Method - Gilang Rizki Padilah; Gina Purnama Insany; Kamdan Kamdan (Fakultas Teknik Universitas Bhayangkara, 2024)
Mountain climbing is a popular activity among the Indonesian community. In the current digital era, websites can serve as an effective platform to facilitate communication and collaboration among mountain climbers. This research aims to design and develop a website for the Indonesian mountain climbing community using PHP, HTML, and CSS programming languages, with a case study on Mount Gede Pangrango. The research methodology includes needs analysis, website design, and implementation. The waterfall method is employed in the system development, and testing is conducted using black box testing and usability methods. In the implementation phase, coding and page design are carried out according to the pre-established design, including color selection, typography, and layout settings. This research results in a website designed and built to facilitate climbers planning to ascend Mount Gede Pangrango. After several trials, the website received overwhelmingly positive responses from respondents, with an average rating of 90%. This result indicates that the website effectively assists users in obtaining information about climbing Mount Gede Pangrango.